Endoscopic Transnasal Skull Base Surgery in Pediatric Patients - Kahilogullari, Gokmen; Meco, Cem; Beton, Suha; Zaimoglu, Murat; Ozgural, Onur; Basak, Hazan; Bozkurt, Melih; Unlu, Agahan (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction In pediatric patients, endoscopic transnasal surgery (ETNS) poses challenges because of the small size of the developing skull and narrow endonasal corridors.Objective This study aimed to evaluate the efficacy of ETNS in children by assessing our experience of endoscopic skull base surgery.Materials and Methods All pediatric patients (n = 54) who were eligible for surgery using only the endonasal endoscopic approach at our tertiary center between 2012 and 2018 were included in this study. The surgeries were performed simultaneously by an endoscopic skull base team of neurosurgeons and otolaryngologists. Hormonal analyses were conducted before and after surgery in all patients with sellar/parasellar lesions. Patients older than 8 years underwent smell and visual testing.Results In the 54 patients aged 1 to 17 years who underwent surgery, craniopharyngioma was the most common pathology (29.6%), followed by pituitary adenoma (22.2%). Gross total resection was achieved in 33 (76.7%) of 41 patients who underwent surgery because of the presence of tumors. All visual deficits improved, although one patient sustained olfactory deterioration. Sixteen (29.6%) patients presented with complications such as transient diabetes insipidus and temporary visual loss.Conclusions Despite anatomy-related challenges in children, adequate results can be achieved with high rates of success, and the functional and anatomical integrity of the developing skull and nose of children can be preserved. In pediatric patients, ETNS is a safe and effective option for addressing various lesions along the skull base.
Keywords: endoscopic; pediatric; skull base; surgery; endonasal; transsphenoidal